2020
DOI: 10.1136/bcr-2019-233582
|View full text |Cite
|
Sign up to set email alerts
|

Cystic lymphangioma of the stomach with marked reactive changes: a rare cause of gastric outlet obstruction in adult

Abstract: Cystic lymphangiomas are benign lymphatic tumours which usually affect the paediatric population and are predominantly located in the head and neck region. Its occurrence during adulthood and an intra-abdominal location are both extremely uncommon. Clinically and radiologically, these lesions often mimic malignancy. Infrequently, these tumours can undergo degenerative and reactive changes obscuring the diagnostic features. We describe hereby an anecdote of cystic lymphangioma with marked reactive chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They may be asymptomatic and can be identified incidentally (18.2%, 4/22). Sometimes, they may have various chief complaints, even could cause gastrointestinal hemorrhage [4] , tumor rupture [5] , gastric outlet obstruction [6] or gastric perforation [7] , depending upon the size and location of a tumor. There are only two cases that gastric lymphangioma coexists with mucosal gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They may be asymptomatic and can be identified incidentally (18.2%, 4/22). Sometimes, they may have various chief complaints, even could cause gastrointestinal hemorrhage [4] , tumor rupture [5] , gastric outlet obstruction [6] or gastric perforation [7] , depending upon the size and location of a tumor. There are only two cases that gastric lymphangioma coexists with mucosal gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They have a wide range of clinical presentations, ranging from asymptomatic to abdominal pain, nausea/vomiting, and distention [ 1 , 3 - 9 ]. Significant complications of these abdominal lymphatic malformations include obstruction, infection, torsion/volvulus, hemorrhage, rupture, and peritonitis [ 5 , 10 - 12 ]. Pediatric patients with abdominal lymphatic malformations tend to present with more acute symptoms as opposed to adults, who tend to be either asymptomatic or present with chronic symptoms [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…He presented with gastric outlet obstruction, and imaging studies found a posterior antral mass, but FNA identified spindle cells. An oncologic gastric resection was performed, and pathology also revealed lymphatic malformation with fibroblastic and myofibroblastic proliferation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the wide application of EUS which could provide valuable information, EUS became one of the most important diagnostic modalities for vascular tumors arising from the gastrointestinal tract ( 11 , 24 ). However, the EUS features of gastric lymphangioma are not well demonstrated, possibly owing to its rarity ( 26 ). In endoscopy, most UGLs are recognized as polyps, and EUS is used to confirm the size and origin of the lesion ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely challenging for the diagnosis of relatively small gastrointestinal lymphangiomas, and histological examination is essential for a definitive diagnosis (26).Margaret et al reported that it was hard to distinguish lymphangioma because of the histologic overlap with lymphangiectasia of the gastrointestinal mucosa (31). Compared with lymphangiectasia, he demonstrated the most reliable histologic features of lymphangioma as the presence of smooth muscle surrounding the lymphatic spaces and complete circumferential lining of spaces by endothelial-type cells (31, 32).…”
Section: Lesions and 5 Patients With Middle-esophageal Lesions In All 14mentioning
confidence: 99%